The role of Valeology in raising a healthy generation - O.R.Parpiyeva; O.O.Dzhaloldinova (Zien Journals, 2022)
In this article, the education of the young generation in any social society is organized on the basis of a specific goal and applied in practice. The purpose of education is determined based on the development of social society, its direction of development, and the content of social relations. The main goal of education organized in the Republic of Uzbekistan today is to bring up a perfect person
Keywords: On Education; Law; National Program of Personnel Training; education